¿Objetividad en las ciencias humanas y sociales? Una reflexión desde la obra de Humberto Maturana (2017)
The objectivity in science has traditionally been associated with the possibility of determining the effects of the events. Thus, determinism and reductionism have been historically inevitable bulwarks of the so-called hard sciences and these epistemological positions have been extrapolated to the human and social sciences, however it is very difficult to achieve a pure objectivity in these Sciences, because of the immeasurable character of social and human processes. The objective is to reflect on the impossibility of objectivity in the social sciences, basically supported by the work of Humberto Maturana. Applies a hermeneutical methodology. The main result concerns the current alternative socio-human orientations do not exceed the theoretical. This is why the conclusion of this article indicates the need to move away for once and for all to positivism and empiricism, not only from the application of methods and qualitative techniques, but from the ontological analysis of the object of study social and human, and the epistemological argument of the subject of research, in correspondence with the ontic analysis. © 2017 Universidad del Zulia.